Peningkatan Hasil Belajar Siswa Kelas X IPA Menggunakan Model Problem Based Learning - Engga Sakti Octaviani; Nyiayu Fahriza Faudiah; Nurjannah Nurjannah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to improve student learning outcomes by using the Problem Based Learning learning model in class X IPA 4 SMA Negeri 2 OKU. This research is a Classroom Action Research (CAR) with a qualitative approach to the Kemmis and Mc. Taggart. This study consisted of several cycles with each cycle consisting of stages, namely planning, action, observation and reflection. The research subjects were 35 students of class X IPA 4 and the object of the research was the results of students' mathematics learning on the subject of Sine and Cosine Rules. The average value of the results of the research in the first cycle was 76.1 with classical completeness of 65.7% and the average value of classical completeness of 85.7%. Based on the results of these studies, it can be concluded that the Problem Based Learning learning model can improve student learning outcomes at X IPA 4 SMA Negeri 2 OKU. Keywords: Study Result, Problem Based Learning Method